579. Acceptability of Home-Based Medical Assessment to Facilitate Re-engagement of HIV-Positive Out-of-Care Persons into Clinical Care, New York City. (26th November 2018) - Udeagu, Chi-Chi; Romano, Anthony; Misra, Kavita; Daskalakis, Demetre
Abstract: Background: For people living with HIV (PLWH), retention in care and antiretroviral treatment improve individual health and curb further HIV transmission. Since 2007, New York City Health Department Disease Intervention Specialists (DIS) make contact attempts to re-engage PLWH presumed to be out-of-care (OOC) because they lack HIV registry report of viral load or CD4 cell count ≥9 months from selection date. Each year, 28–50% of OOC-PLWH refuse assistance from DIS to re-engage in HIV care. In 2017, we assessed the interest of OOC-PLWH in a medical home visit to facilitate their re-engagement in HIV care. Home visits could help DIS circumvent barriers to care re-engagement: privacy issues, impaired mobility and chronic health conditions, and by providing discreet and accessible medical care. Methods: From January to December 2017, DIS interviewed 847 OOC-PLWH and administered a questionnaire to ascertain their interest in a home visit to evaluate their general and HIV-related health status (e.g., physical and HIV evaluation, health education, sexually transmitted diseases [STD] and hepatitis C [HCV] screening). Results: Of the 847 OOC-PLWH interviewed, 111 (13%) were interested in home visits. The majority of participants were male (69%), non-Hispanic black (60%) and had a median age of 47 years at intervention (range: 19–88). Thirty-eight percent were men who had sex with men. Higher proportions of those interested accepted care appointments (93% vs. 73%) and kept a clinic appointment (78% vs. 61%). Compared with non-Hispanic blacks, Hispanics were less likely to be interested in home visits (aOR: 0.59; 95% CI: 0.36–0.96). Compared with persons who accepted an HIV care appointment, persons who did not were significantly more likely to express interest in home visits (aOR: 4.18; 95% CI: 1.62–10.78). Those expressing general interest had specific interest in assessments for HIV-related blood tests (85%), medication (84%) or education (78%), as well as general health evaluation and screening for HCV (68%) or STD (64%). Conclusion: Our assessment suggests that medical home visits could improve re-engagement rates among OOC-PLWH. Lower interest among Hispanic patients suggests that future efforts should be sensitive to community needs and concerns. Disclosures: All authors: No reported disclosures.